Inflammatory and chemotactic signals of the brainstem solitary tract mediate the morphine exacerbation of impaired reflex chronotropism in septic rats - Abdelnaby, Mohamed; Sallam, Marwa Y.; Helmy, Mai M.; El-Gowelli, Hanan M.; Rao, Muddanna S.; El-Mas, Mahmoud M. (Frontiers in Pharmacology, 2026)
IntroductionThe interplay between opioid analgesics and sepsis in intensive care units (ICUs) is multifaceted, often amplifying immune dysregulation and adversely affecting cardiovascular outcomes.AimWe investigated whether morphine, the prototypical opioid, influences sepsis-induced impairment of arterial baroreceptor function and the accompanying inflammation.MethodsRats were implanted with indwelling catheters in femoral vessels and intracisternal (i.c.) space, and sepsis was induced using the cecal ligation and puncture (CLP) technique. The baroreceptor-mediated control of chronotropic activity was assessed 24 h later in awake rats using the vasoactive method, which relates blood pressure changes caused by i.v. phenylephrine (PE) or sodium nitroprusside (SNP) to respective reciprocal changes in heart rate.ResultsThe treatment of sham rats with morphine or induction of sepsis led to comparable attenuations of reflex decrements and increments in chronotropic responses and decreases in slopes of baroreflex curves (baroreflex sensitivity, BRS). The treatment of septic rats with morphine further amplified the decline in reflex bradycardic (BRSPE), but not tachycardic (BRSSNP), and this exaggerated bradycardia disappeared after (i) systemic blockade of opioid receptors by i.v. morphine or (ii) selective central inhibition of PI3K, MAPK-ERK, MAPK-JNK, NADPHox), or Rho-kinase (ROCK). These pharmacological interventions also attenuated the elevated protein expression of toll-like receptor 4 (TLR4) and monocyte chemoattractant protein-1 (MCP1) in the brainstem nucleus tractus solitarius (NTS) of morphine-treated CLP rats.ConclusionOverall, morphine augments the sepsis-induced depression of reflex cardiovagal activity through an opioid receptor sensitive mechanism that engages brainstem inflammatory and chemotactic circuits related to PI3K/MAPK/NADPHox/ROCK signaling.